Study of andrographolide bioactivity against Pseudomonas aeruginosa based on computational methodology and biochemical analysis - He, Lihui; Song, Lai; Li, Xuanhao; Lin, Shibo; Ye, Guodong; Liu, Huanxiang; Zhao, Xiaotian (Frontiers in Chemistry, 2024)
Andrographolide is one of the main biologically active molecules isolated from Andrographis paniculata (A. paniculata) which is a traditional Chinese herb used extensively throughout Eastern Asia, India and China. Pseudomonas aeruginosa, often known as P. aeruginosa, is a common clinical opportunistic pathogen with remarkable adaptability to harsh settings and resistance to antibiotics. P. aeruginosa possesses a wide array of virulence traits that biofilm is one of them which contribute to its pathogenicity. One of the main modulators of P. aeruginosa controlled intramembrane proteolysis pathway is AlgW, a membrane-bound periplasmic serine protease. In this work, we have used a set of Density Functional Theory (DFT) calculations to understand the variety of chemical parameters in details between andrographolide and levofloxacin which is shows strong bactericidal activity against P. aeruginosa. Additionally, the stability and interaction of andrographolide and levofloxacin with the protein AlgW have been investigated by Molecular Docking and Molecular Dynamics Simulation (MD). Moreover, the growth and inhibition the biofilm production of P. aeruginosa experiments was also investigated and give us a view that andrographolide could be a potential natural product to inhibit the P. aeruginosa.